The origins of the spanish railroad accounting model: a qualitative study of the MZA’S operating account (1856-1874) - Santos Cabalgante, Beatriz; Fidalgo Cerviño, Esther; Santos Cebrián, Mónica (De Computis, Revista Española de Historia de la Contabilidad., 2014)
The lack of external regulation about the form and substance of the financial statements that railroad companies had to report during the implementation phase of the Spanish railway, meant that each company developed its own accounting model. In this study we have described, analysed and interpreted the more relevant changes in the accounting information in relation to the business result. Using the analysis of an historical case, we developed an ad-hoc research tool, for recording all the changes of the operating account. The results of the study prove that MZA’s operating account reflected the particularities of the railway business although subject to limitations, and the reported information improved during the study period in terms of relevance and reliability.